2016
DOI: 10.1016/j.lingua.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Intervention effects and Relativized Minimality: New experimental evidence from graded judgments

Abstract: Abstract+ Models LINGUA-2417; No. of Pages 21 Please cite this article in press as: Villata, S., et al., Intervention effects and Relativized Minimality: New experimental evidence from graded judgments. Lingua (2016) AbstractAccording to Featural Relativized Minimality, the local relation between an extracted element and its trace is disrupted when it crosses an intervening element whose morphosyntactic featural specification matches the specification of the elements it separates. This approach naturally l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 24 publications
4
40
0
1
Order By: Relevance
“…8 These results are challenging for a featural Relativized Minimality (fRM) account of 3DO clitic omission and production errors. According to fRM (Rizzi, 1990(Rizzi, , 2001(Rizzi, , 2004, the local relation between an extracted element and its origin is disrupted when there is an intervening element whose morphosyntactic featural specification matches the specification of the extracted element [see Villata et al (2016) for discussion and experimental findings with adults]. Acquisition studies on relative clause and wh-question in a fRM model showed that an inclusion relation between the feature set of intervener and the feature set of the extracted element disrupts the local relation between an extracted element and its origin in children (Friedmann et al, 2009;Belletti et al, 2012;Contemori and Belletti, 2013) As we discussed, the external verb argument acts as intervener between the clitic (or pro) and its origin during DO clitic derivation and it is endowed with a subset of features of the clitic.…”
Section: Discussionmentioning
confidence: 99%
“…8 These results are challenging for a featural Relativized Minimality (fRM) account of 3DO clitic omission and production errors. According to fRM (Rizzi, 1990(Rizzi, , 2001(Rizzi, , 2004, the local relation between an extracted element and its origin is disrupted when there is an intervening element whose morphosyntactic featural specification matches the specification of the extracted element [see Villata et al (2016) for discussion and experimental findings with adults]. Acquisition studies on relative clause and wh-question in a fRM model showed that an inclusion relation between the feature set of intervener and the feature set of the extracted element disrupts the local relation between an extracted element and its origin in children (Friedmann et al, 2009;Belletti et al, 2012;Contemori and Belletti, 2013) As we discussed, the external verb argument acts as intervener between the clitic (or pro) and its origin during DO clitic derivation and it is endowed with a subset of features of the clitic.…”
Section: Discussionmentioning
confidence: 99%
“…Our prediction regarding a potential WM modulation of island effects (as well as our choice of WM test) was based on the assumptions of capacity models about the role of memory during language processing (e.g., Just & Carpenter 1992). However, capacity-based models have more recently been superseded by processing models that view comprehension as involving cue-based memory retrieval (e.g., McElree et al 2003;Lewis et al 2006), and it has been proposed that some types of island effects could be accounted for in this framework (Ortega-Santos 2011; Atkinson et al 2016;Villata et al 2016). From the point of view of these models, WM scores that reflect the ability to recall serial order information might not necessarily correlate with comprehension difficulty (Gieselman et al 2013;see also Van Dyke et al 2014).…”
Section: Interrogative Islandsmentioning
confidence: 99%
“…In these configurations, note that interveners are not arbitrarily determined. In a number of studies (S-S , Beck 2006, Rizzi 2013, S. Villata et al 2016, it has been shown that an 'intervener' is described as an element that shares a set of identical features with a phrase that attempts to occupy a (semantically or syntactically) higher position than the potential intervener. Among others, according to Rizzi's (2013) revised featural Relativized Minimality (henceforth fRM), the degree of feature sharing between a crossing-over element and a crossed-over element determines how acceptable the relevant sentence is.…”
Section: Superiority Effects (3) a Who Did You Persuadementioning
confidence: 99%
“…It has been suggested that the prohibition of extraction of the second wh-word is attributed to the intervention effect of the first wh-word in the two structures (Rizzi (1990(Rizzi ( , 2013, Pesetsky (2013), Hofmeister et al 2013and S. Villata et al (2016)). Adopting this perspective, wh-islands and superiority-violating wh-questions will be considered as intervention phenomena.…”
Section: Wh-island Effects and Superiority Effectsmentioning
confidence: 99%